Atviros Lietuvos knyga ekspertų požiūriu - Poviliūnas, Arūnas (Knygotyra, 2003)
Evaluation of the academic literature publishing in Lithuania was twofold. Some of the expertsestimated situation as critical, others stressed the obvious improvement in the field of academicpublishing. Skeptics appealed to the state authorities, which do not have clear policy of academicpublishing and moreover, do not give support to it. Optimists enjoyed newly published books anddoubted ability of the state authorities to coordinate academic publishing. Intellectual and academicdiscourses are constructed from the local knowledge and the totality of it cannot be graspedfrom one generalizing point. But experts agreed that limited resources determine the need of clearpriorities in academic publishing.The publishing of the intellectual and academic literature face different problems that comefrom its specific conditions. An academic book is more expensive because its number of copiesand circulation is smaller. The reader of an academic book is more educated, knows foreignlanguages and this limits the market of academic translations. Academic field is specialized andit requires very different and special texts. Academic texts, this is based on the special traits ofacademic field, have longer period of consumption and this also causes additional finance problemsfor publishers.All experts agreed that Programme The Books for an Open Society is very important foracademic publishing and helps solving the problems that it faces nowadays. The Programme helpedpublishers of academic, non-commercial literature to begin their work.Experts thought that main target reader of the Programme The Books for an Open Societybooks is contemporary and future intellectual elite. But academic, intellectual society is veryfragmented and differs by academic disciplines and degree of socialization into academic community,etc. Moreover, big part of potential readers of Programme book has rather narrow specializationand "lives" in its own professional "cell". At the same time, there is competition betweenacademic groups that causes marketing problems for publishers. But younger generation ofacademic community is more mass consumer of academic literature.Experts agree that the Programme The Books for an Open Society reflects general tendenciesin social and humanitarian sciences, but stressed that there are factors that influence this reflection.These factors are ideological priorities of the Programme, more attention to Anglo-Saxon tradition,not equal sympathy for different academic disciplines. Experts also stressed that publishing of nonfictiontranslations always will be retarded because only the books that are already recognized inWestern academic community are selected for translation and publishing. Further discussion provedthat Programme The Books for an Open Society is an organic part of Lithuania's academic fieldand at the same time reflects all its subtleties.Discussion of experts about the quality of the Programme's books concentrated on the qualityof translations. Discussion demonstrated that there is a non-cooperational relationship betweenpublishers and editors on the one side and translators on the other and this situation inevitablyinfluences the quality of the published book. It came out, that the Programme did not find a wayout of this problematic situation. Pilot translations as such could not change the situation andthey often remained only a way to control. But experts recognized that the publishing activitiesof the Programme The Books for an Open Society and Open Society Fund-Lithuania in generalwere very important in raising good new translators.Experts mentioned following shortages of the Programme The Books for an Open Society:(1) The Programme by being ideologically engaged, inevitably supported only some of academictendencies; (2) The Programme could have supported original Lithuanian books and textbooks.This could enrich the academic discourse already opened by translations; (3) Experts noticed thatthe Programme favours some academic disciplines at the cost of others; (4) Experts thought thatthe Programme also favours fundamental academic publications at the cost of more ephemeral butpopular academic books; (5) Some facts from books publishing proves that criteria used in selectingbooks for publishing under the Programme title are not clear enough.Experts also discussed the possible reasons that caused mentioned shortcomings of theprogramme, especially the quality of translations. One of reasons was that institutional resourcesof publishing houses during the accomplishment of the Programme were not enough to realize thepossibilities which have appeared when OSF-L publishing programmes (The Books for an OpenSociety and publishing activities of the Programme Education for the Future of Lithuania) havejoined the publishing market of Lithuania. The lack of institutional resources for the effectiveuse of the new financial possibilities sometimes has negatively influenced the quality of thepublished books.Experts recommend to pay more attention to the publishing of dictionaries of social sciencesand humanities – more summarizing, synthesizing books, which would represent achievements notonly of Anglo-Saxon tradition. Proportions between published books of different academic disciplinesare to be followed more precisely. Especially in publishing dictionaries, new technologiescould be used more often (CD-ROM etc.).